Geographic Representation in Party‐Dominated Legislatures: A Quantitative Text Analysis of Parliamentary Questions in the German Bundestag. Issue 4 (15th March 2019) - Zittel, Thomas; Nyhuis, Dominic; Baumann, Markus
Abstract : Political representation in European democracies is widely considered partisan and collectivist. This article, however, stresses that there is more to the representative process in European democracies than just its textbook version. It emphasizes the role of geographic representation as a complementary strategy in party‐dominated legislatures that is characterized by two distinct features. First, legislators employ distinct opportunities to participate in legislative contexts to signal attention to geographic constituents without disrupting party unity. Second, these activities are motivated by individual‐ and district‐level characteristics that supplement electoral‐system‐level sources of geographic representation. We empirically test and corroborate this argument for the German case on the basis of a content analysis of parliamentary questions in the 17th German Bundestag (2009–13). In this analysis, we show that higher levels of localness among legislators and higher levels of electoral volatility in districts result in increased geographic representation.